ETHICAL ASPECTS IN TAX AVOIDANCE A COMPARATIVE STUDY BETWEEN THE PERSPECTIVE OF STUDENTS WHO HAVE BEEN WORKING AND PRIVATE EMPLOYEES IN YOGYAKARTA - Novriyandana, Rifqi; one, Dr. Prihantoro (Accounting, 2010)
This research was conducted on the basis of replication of previous studies that have been done in various countries around the world. The study was conducted in one state in America that is Utah. This research was conducted by Robert W. Mc Gee and R. Sheldon Smith (2006) study was based on a hot debate for more than 500 years in terms of theology and philosophy and has always been a debate between researchers who view from various perspectives and underlying conditions of this study is whether that tax evasion can be justified, and whether tax levy is an ethical one for all the people who are in a country. Every country has its own characteristics, so that research results from one country and other countries do not necessarily show the same results. There are several issues that serve as guidelines in conducting research that is derived from Crowe (1944), a survey on the students to know the level of agreement or disagreement on 15 issues that evolved from ancient times, and 3 issues are now being developed. This research is intended for every opinion issued by the respondent to know where the statement is the highest level and note also the lowest level in the perspective of valuation tax evasion, and also unknown whether there are differences in point of view of society with different backgrounds work of public servants and self-employed or entrepreneurs. On the issues that develop from long ago up to now the debate is the background from various perspectives that include the point of view of philosophy, psychology, theology, and through the point of view of various religions that exist, then also be seen from the perspective of the background learned science and gender, such as research McGee and Lingle (2005) whose research was conducted in Guatemala. But, unlike the results in other countries such as in research in Germany and Romania.Based on the above items in this study found that working students and private employees there was no difference of views on the ethical aspects of tax evasion. Then it is felt the most natural to do so is tax evasion because the tax system is unfair to taxpayers. Keywords: Tax evasion, differences perspective